(untitled) (Revista Brasileira Multidisciplinar, 2022)
Self-medication is defined as the administration of medication without medical advice or prescription, with the patient himself who decides which drug will be used. The consumption of non-prescription medications, despite the risks, has become a very common practice in the Brazilian population in times of pandemic. This study aimed to investigate the prevalence of the main causes of self-medication in times of the COVID-19 pandemic, focusing on some cities in the state of Paraiba. Data collection took place through a questionnaire accessed via Google Forms, with sociodemographic and medicated questions. 95.7% of the participants reported practicing self-medication and 61.6% self-medicating due to the pandemic. The most prevalent therapeutic class was analgesics, followed by antiparasitic drugs. The main drugs used are dipyrone, paracetamol and ivermectin. The main associated symptoms are headache and influenza/cold/cough. Among the main factors associated with self-medication, practicality and comorbidity and the ease of buying at the pharmacy are noteworthy. In this way, the performance of the pharmacist can prevent self-medication, thus playing an important role in patient care.